Application and biosafety of nano-copper in sports engineering. (30th September 2020) - Zhu, Yong
Nanomaterials have been widely used in stadiums, sports lawns, athletics tracks, sportswear, sports equipment and sports supplements. However, the entry of nanomaterials into the body may also bring negative effects on cells, lung tissue, liver and kidney tissue, and brain tissue. Also, there are certain hidden dangers of biosecurity. While making full use of the positive effects of nanomaterials on the development of sports engineering, the negative impact of nanomaterials on the environment and human health has also attracted people's attention. Although much research has been done on the toxicity of persistent organic pollutants in the environment, few studies have been conducted on the toxicity of nanomaterials and persistent pollutants. Based on this, this paper mainly analyses the toxic effects and mechanisms of nano-copper in common sports applications using whole-cell biosensors that respond to various stresses. After 30 min of exposure to bacteria, the toxic effect of nano-copper can be quickly detected. Nano-copper can induce a variety of cell damage, including oxidative stress, DNA damage, protein damage and cell membrane damage, resulting in significant cytotoxicity. The generation of hydrogen peroxide caused by Cu (I) released from the nano-copper solution proved to be the main source of nano-copper toxicity. Nano-copper is adsorbed and internalised by cells, which may aggravate the damage to the cells. In contrast, micron copper is relatively stable and almost non-toxic. In addition, Cu (II) can induce protein damage, cell membrane damage, and minor DNA damage only at relatively high concentrations. Therefore, this study shows that whole-cell bacterial sensors that can respond to various stresses are an efficient way to screen for nanoparticle toxicity. And it can be used to clarify the mechanism of toxicity of nano-copper.